2-Heteroarylimino-5-arylidene-4-thiazolidinones as a new class of non-nucleoside inhibitors of HCV NS5B polymerase - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2013)
Hepatitis C virus (HCV) NS5B polymerase is an important and attractive target for the development of anti-HCV drugs. Here we report on the design, synthesis and evaluation of twenty-four novel allosteric inhibitors bearing the 4-thiazolidinone scaffold as inhibitors of HCV NS5B polymerase. Eleven compounds tested were found to inhibit HCV NS5B with IC50 values ranging between 19.8 and 64.9 RM. Compound 24 was the most active of this series with an IC50 of 5.6 mu M. A number of these derivatives further exhibited strong inhibition against HCV lb and 2a genotypes in cell based antiviral assays. Molecular docking analysis predicted that the thiazolidinone derivatives bind to the NS5B thumb pocketII (TP-II). Our results suggest that further optimization of the thiazolidinone scaffold may be possible to yield new derivatives with improved enzyme- and cell-based activity. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Antiviral agents; Hepatitis C; HCV NS5B polymerase; Thiazolidinones; DEPENDENT RNA-POLYMERASE; C VIRUS-INFECTION; ANTIMICROBIAL ACTIVITY; CRYSTAL-STRUCTURE; IN-VITRO; BIOLOGICAL EVALUATION; HEPATITIS; 4-THIAZOLIDINONES; DERIVATIVES; DESIGN